Factors Influencing the Psychological Well-Being of EFL Students in a Boarding University Environment - Jessenianta, Aurel Keisha; Khoir, Azizatul; Amara, Azka; Rohmana, Wahyu Indah Mala (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study investigates the factors influencing the psychological well-being of EFL (English as a Foreign Language) students living in university dormitories. The issue of student well-being has gained increasing attention as dormitory life can significantly shape students’ academic performance, social adjustment, and emotional balance. The main objective of this research is to identify and analyze the internal and external factors that affect students’ mental and emotional well-being within the dormitory environment. The study employed a qualitative approach using semi-structured interviews with selected EFL students from a university in Indonesia. Data were analyzed thematically to explore recurring patterns and experiences related to psychological well-being. The findings indicate that several key factors influence students’ well-being, including social support, academic pressure, adaptability to dormitory life, and personal motivation. Supportive peer relationships and effective time management were found to enhance students’ psychological well-being, whereas homesickness and excessive workload often reduced their emotional stability. The study concludes that maintaining a balanced social and academic environment in dormitories is crucial for sustaining students’ well-being. It also suggests that universities should provide targeted counseling and peer mentoring programs to help students cope with emotional and academic challenges. These findings contribute to the growing body of research on student mental health and offer practical insights for improving the dormitory experience of EFL learners.